2012
DOI: 10.1016/j.neulet.2012.10.028
|View full text |Cite
|
Sign up to set email alerts
|

One's own name distorts visual space

Abstract: Here, we demonstrated that one's own name attracts the subjective location of a visual target. We simultaneously presented observers their own name and others' name in the left and right visual fields. A target circle was presented for 53 ms around the center of the display 200 ms after the names disappeared. Ten observers were required to manually reproduce the target location by pointing with the mouse. The results indicated that the observers significantly mislocalized the target 1.61' on average toward the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…As a highly abstract social identity, the rapid identification of names has become a research hotspot [ 6 ], and names have gradually become a common stimulus in self-cognition [ 43 ]. In the self-name recognition experiment, Harris [ 39 ] studied the self-name fast search problem through nine visual search experiments.…”
Section: Behavioral Uniqueness Of Self-awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…As a highly abstract social identity, the rapid identification of names has become a research hotspot [ 6 ], and names have gradually become a common stimulus in self-cognition [ 43 ]. In the self-name recognition experiment, Harris [ 39 ] studied the self-name fast search problem through nine visual search experiments.…”
Section: Behavioral Uniqueness Of Self-awarenessmentioning
confidence: 99%
“…Eye movement data showed that the subjects only stayed on their own faces for a longer time, which proved that their own faces were more difficult to disengage. In addition to the strong interference of self-face, Yamada [ 43 ] found that abstract information about his name also inhibited target stimuli. In the experiment, the visual search task of the target point was designed, and the results showed that when the subjects’ own name appeared as an interference, the average deviation of the eye movement error of the target point positioning was 1.61°.…”
Section: Behavioral Uniqueness Of Self-awarenessmentioning
confidence: 99%
“…In the present study, therefore, we conducted two experiments with different parameters and designs to investigate whether the SRE occurs by implicit self-referential processing evoked by the self-related stimulus that was presented without participants realizing. We focused on participants’ own name as the self-related stimulus because many studies have been done that have indicated special features of the own-name just like own-face ( Shapiro et al, 1997 ; Tacikowski et al, 2011 , 2013 ; Zhao et al, 2011 ; Yamada et al, 2012 ; Nakane et al, 2016 ). For example, Shapiro et al (1997) indicated that participants could detect their own name better as a second target in a rapid serial visual presentation (RSVP) stream than another person’s name or a noun.…”
Section: Introductionmentioning
confidence: 99%
“…This type of mislocalization occurs because the neural sensitivity of position coding units is inhibited around a focus of attention, and this inhibition resultantly shifts the spatial centroids of population activities of the unit, coding a target location away from the pre-cued location (Suzuki & Cavanagh, 1997). On the other hand, a memorized location of a target is reproduced with a bias toward a pre-cued location (Yamada, Kawabe, & Miura, 2008b, 2012Yamada, Miura, & Kawabe, 2011). The researchers suggest that the spatial distribution of attention modulates location signals of the target around the pre-cued location, and this leads to the mislocalization of the target toward the pre-cued location (Yamada et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that investigated the mislocalization of a target have employed a cueing paradigm in which external objects were presented to control the location of observers' attentional focus. Because those external objects (such as a bright rectangle) have retinal stimulations at a cued location (e.g., Yamada et al, 2011Yamada et al, , 2012, most of the previous findings are consistent with an idea that the mislocalization of a target towards the external object is caused by memory averaging between a target and an attended external object (Kerzel, 2002). Alternatively, however, it was also possible that the mislocalization of a target occurs because a location signal of a target is directly modulated by spatial distribution of observers' attention.…”
Section: Introductionmentioning
confidence: 99%